New Switching System of Railway Division Communication - Xu Di and Zhao Jianren (Tongxin xuebao)
In this paper, the problem of automatization of the railway division communication it described. Because the railway communication network is developed toward ISDN, it requires the railway division communication followed to develop. The system analysis of the railway division communication is introduced, the new system structure and the signalling form are suggested, the programme modules and data modules of designing soffware are showed in the paper. The system soffware is run in simulant operation by the computer, that system being realizable is proofed.